Phenotypic Diversity of Lactobacillus sakei Strains - Montanari, Chiara; Barbieri, Federica; Magnani, Michael; Grazia, Luigi; Gardini, Fausto; Tabanelli, Giulia (Frontiers in Microbiology, 2018)
Lactobacillus sakei is a LAB species highly adapted to the meat environment. For this reason, selected strains are often used as starter culture in the production of fermented sausages, especially in Mediterranean countries. It often represents the dominant species in these products and can maintain its viability during all the ripening period, which can take also some months. This ability is guaranteed by the possibility of the species to obtain energy through pathways active even when hexoses are depleted. This species is characterized by a relevant genetic and phenotypic diversity and its metabolism can be further affected by the growth condition applied. In this work we investigate the metabolic responses of six different L. sakei in a synthetic medium (DM) containing defined amounts of amino acids in relation to temperature and NaCl concentration. In addition, the activities of cells pre-grown in presence of glucose o ribose were tested. Arginine was efficiently up-taken with the exception of the type strain DSMZ 20017t. Other amino acids (i.e. serine, asparagine, cysteine, methionine) were metabolized through potentially energetic pathways which start from pyruvate accumulation, as demonstrated by the organic acid accumulation trend in the condition tested, especially in DM without sugar added. The presence of excesses of pyruvate deriving from amino acids lead to the accumulation of diacetyl and acetoin by all the strains when sugars were added. This approach allowed a deeper insight into the phenotypic variability of the species and improved the comprehension of the metabolic pathways adopted by L. sakei to survive and grow in restrictive conditions such as those found in fermented sausages during fermentations. Thus, the results obtained are useful information for improving and optimizing the use of such strains as starter culture for these products.